Wayfarer - Joshua Cupps (Stimulus: A Medical Humanities Journal, 2023)
“Be in this world as though you were a stranger or a wayfarer.” Hadith 40, Sahih al-Bukhari. "Wayfarer" is inspired by my favorite Hadith, or teaching from the life of Prophet Mohammad, peace be upon him. This piece reflects the difficulty of the traveler on their journey home in the hereafter. I wanted to show my own struggle in this journey, especially as someone who has accepted this new way of life. I wanted to show that it is a constant battle of faith that is not always linear, stumbling and falling along the way. However, finding strength in surrendering to a higher will and trusting in it allows me to bear the weight of the challenges ahead. Ultimately, it is "صَبْرٌ", or patience, with myself and in a greater plan that gives me peace in this journey.